Cyprus : Detailed Assessments of Observance of Standards and Codes for Banking Supervision, Insurance Supervision, and Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2006)
The Compliance of the Basel Core Principles welcomes the assessors' recognition of the overall quality and effectiveness of Cyprus's banking regulatory and supervisory framework in place, and the resulting high degree of compliance with the Basel Core Principles. Regulation has to be defined to set a frame in which insurance undertakings can operate. Clear objectives and measures should be defined for the Superintendent of Insurance. The International Organization of Securities Commissions Principles was assessed in accordance with the criteria in the Guidance Note.